Data Collection Procedures for School‐Based Surveys Among Adolescents: The Youth in Europe Study. (23rd July 2013) - Kristjansson, Alfgeir Logi; Sigfusson, Jon; Sigfusdottir, Inga Dora; Allegrante, John P.
ABSTRACT: BACKGROUND: Collection of valid and reliable surveillance data as a basis for school health promotion and education policy and practice for children and adolescence is of great importance. However, numerous methodological and practical problems arise in the planning and collection of such survey data that need to be resolved in order to ensure the validity of the data and to maximize the response rate without being prohibitively costly. METHOD: This article builds on a 15‐yearlong experience of such annual data collections in Iceland and describes the preparation, process, and collection of data that provide a common methodologic framework for the school‐based survey, Youth in Europe, a population‐based survey of 14‐ to 16‐year‐old adolescents, being collected across 18 European cities now participating in the European Cities Against Drugs (ECAD) program. RESULTS: We identified 11 critical steps for developing and implementing the surveys in light of the recent literature on the preparation and implementation practices in school‐based data collection among adolescents. CONCLUSION: Limiting the disruption of daily operations in schools while at the same time ensuring both quality and clarity of data collection procedures in school‐based surveys are of paramount importance for researchers, school personnel, and students.